Pk/pd analysis by nonlinear mixed‐effects modeling of a marbofloxacin dose regimen for treatment of goat mastitis produced by coagulase‐negative staphylococci - Lorenzutti, Augusto Matías (2021)
Coagulase‐negative staphylococci are main pathogens that produce goat mastitis. Mar-bofloxacin is a third‐generation fluoroquinolone approved for treat mastitis in animals. The objec-tives of this study were: (i) to determine the pharmacokinetics of marbofloxacin (10 mg/kg/24 h) in serum and milk administered intramuscularly for five days in goats with mastitis induced by coag-ulase‐negative staphylococci; (ii) to characterize the concentration–effect relationship of marboflox-acin against coagulase‐negative staphylococci in Mueller Hinton broth and goat milk; (iii) to determine AUC/MIC cutoff values of marbofloxacin, and iv) to perform a PK/PD analysis to evaluate the efficacy of the dose regimen for the treatment of goat mastitis produced by coagulase‐negative staphylococci. Marbofloxacin presented context‐sensitive pharmacokinetics, influenced by the evolution of the disease, which decreased marbofloxacin disposition in serum and milk. Marbofloxacin showed a median (95%CI) fAUC/MIC values for MIC of 0.4 and 0.8 μg/mL of 26.66 (22.26–36.64) and 32.28 (26.57–48.35) related with −2 log10CFU/mL reduction; and 32.26 (24.81–81.50) and 41.39 (29.38–128.01) for −3 log10CFU/mL reduction in Mueller Hinton broth. For milk, −2 log10CFU/mL reduction was achieved with 41.48 (35.29–58.73) and 51.91 (39.09–131.63), and −3 log10CFU/mL reduction with 51.04 (41.6–82.1) and 65.65 (46.68–210.16). The proposed dose regimen was adequate for the treatment of goat mastitis produced by coagulase‐negative staphylococci, resulting in microbiological and clinical cure of all animals. The animal model used in this study provided important pharmacokinetic information about the effect of the infection on the pharmacokinetics of marboflox-acin. Pharmacodynamic modeling showed that fAUC/MIC cutoff values were higher in goat milk compared with Mueller Hinton broth.